Exosomal non coding RNAs as a novel target for diabetes mellitus and its complications - Albert Sufianov; Andrey Kostin; Sema Begliarzade; Valentin Kudriashov; Tatiana Ilyasova; Yanchao Liang; Albert Mukhamedzyanov; Ozal Beylerli (Non-coding RNA Research, 2023)
Diabetes mellitus (DM) is a first-line priority among the problems facing medical science and public health in almost all countries of the world. The main problem of DM is the high incidence of damage to the cardiovascular system, which in turn leads to diseases such as myocardial infarction, stroke, gangrene of the lower extremities, blindness and chronic renal failure. As a result, the study of the molecular genetic mechanisms of the pathogenesis of DM is of critical importance for the development of new diagnostic and therapeutic strategies. Molecular genetic aspects of the etiology and pathogenesis of diabetes mellitus are intensively studied in well-known laboratories around the world. One of the strategies in this direction is to study the role of exosomes in the pathogenesis of DM. Exosomes are microscopic extracellular vesicles with a diameter of 30–100 nm, released into the intercellular space by cells of various tissues and organs. The content of exosomes depends on the cell type and includes mRNA, non-coding RNAs, DNA, and so on. Non-coding RNAs, a group of RNAs with limited transcriptional activity, have been discovered to play a significant role in regulating gene expression through epigenetic and posttranscriptional modulation, such as silencing of messenger RNA. One of the problems of usage exosomes in DM is the identification of the cellular origin of exosomes and the standardization of protocols for molecular genetic studies in clinical laboratories. In addition, the question of the target orientation of exosomes and their targeted activity requires additional study. Solving these and other problems will make it possible to use exosomes for the diagnosis and delivery of drugs directly to target cells in DM. This study presents an analysis of literature data on the role of exosomes and ncRNAs in the development and progression of DM, as well as the prospects for the use of exosomes in clinical practice in this disease.